2012
DOI: 10.1080/02772248.2012.657199
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of acute mercury toxicity by a novel, non-toxic lipid soluble chelator N,N′bis-(2-mercaptoethyl)isophthalamide: effect on animal survival, health, mercury excretion, and organ accumulation

Abstract: The toxic effects of mercury are known to be complex with specific enzyme inhibitions and subsequent oxidative stress adding to the damaging effects. There are likely other factors involved, such as the development of impaired metal ion homeostasis and depletion of thiol and selenium based metabolites such as cysteine and selenium. Much of the toxicity of mercury occurs at the intracellular level via binding of Hg 2+ to thiol groups in specific proteins. Therefore, amelioration of mercury toxicity by the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…NBMI consists of two thiol groups linked via a pair of amide groups. It was originally developed as a precipitation agent for the removal of soft metals from water [ 9 ]. Using a stoichiometric 1:1 M ratio of NBMI to Pb, 99.4 % of Pb could be removed from samples in a lead battery recycling site [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…NBMI consists of two thiol groups linked via a pair of amide groups. It was originally developed as a precipitation agent for the removal of soft metals from water [ 9 ]. Using a stoichiometric 1:1 M ratio of NBMI to Pb, 99.4 % of Pb could be removed from samples in a lead battery recycling site [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…These smaller studies are needed to test outcomes, infrastructure, study parameters and local circumstances and to avoid problems in following bigger and more expensive studies. While its cytoprotective, anti-oxidative properties and its impact on acute Hg intoxication in rats are already proven [ 22 24 ], the aim of this pilot study was to gain first knowledge about the efficacy of NBMI on chronic mercury intoxication in humans.
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…NAC and NBMI have previously been identified as scavengers for reactive oxygen species (ROS) in vitro . In this study, both NBMI and NAC were able entrap the electrophilic paracetamol metabolites NAPQI and p‐BQ as reflected by their ability to block hTRPA1 activation (fig.…”
Section: Resultsmentioning
confidence: 81%
“…Interestingly, NBMI is known to cross cellular membranes and accumulate in the liver, the site where ROS and NAPQI are predominantly produced during paracetamol overdosing. Metabolic profiling with human liver microsomes has indicated that NBMI acts as a highly efficient scavenger of hydroxyl‐free radicals as each thiol group can interact and stabilize several radical oxygens . Thus, in vitro data suggest that NBMI is able to entrap electrophilic paracetamol metabolites, which initiate the hepatotoxic process , and to efficiently bind oxidative stress‐mediated products responsible for the progression and generation of paracetamol‐induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation